Older adults' experiences, needs, and preferences for community park design in China: a reflexive thematic analysis - Zhongjun, Tao; Maruthaveeran, Sreetheran; Shahidan, Mohd Fairuz; Yanci, Xiang (Elsevier GmbH, 2025)
This study explores the views and experiences of older adults in Changsha, Hunan Province, China regarding community park activities, evaluates their support needs, and offers recommendations for future community park construction and renovation. We conducted walk-along interviews with 47 participants (aged 55 and above) from six different community parks. Reflexive thematic analysis revealed that older adults perceive current community park designs as failing to meet their real needs. Understanding the true needs of older adults is crucial for improving community park design and promoting their physical and mental well-being. This study uses reflexive thematic analysis to explore older adults' experiences, needs, and preferences regarding community park design in Changsha city. Guided by an integrative design approach, the findings highlight the importance of addressing the heterogeneity within the older adult population and incorporating elements of community cultural history into park planning. Traditional designs often lack authenticity and fail to meet the diverse needs of older adults. Future park designs should prioritize creating spaces that foster social interaction, integrate parks into the daily lives of older adults, and reflect local cultural contexts.